Investigating Changes in Student Teachers’ Schema during Teaching Practicum Using Metaphor - Halim, Abdul; Safei, Nur Hasanah; Yunianti, Siswah (AL LUGHAWIYAAT, 2024)
This study addresses the scheme changes of negative and positive emotion encountered by the student teachers (STs) in the course of teaching practicum. To comprehend this problem, this study explores the use of metaphors before and toward the end of teaching practicum. To gather data, 32 STs were asked to write a reflective journal. This reflective journal is coded and analyzed thematically. This study reveals that the use of metaphors could facilitate the STs to express their emotion naturally. Before teaching practicum, STs used the following metaphors: animals, feeling, objects, and natural phenomena, while toward the end of teaching practicum, STs the following metaphors: animals, parts of the body, sport, effort, hero, feeling, objects, natural phenomena, and plants. Such metaphors revealed that the majority of STs experienced both difficulties and enjoyment in these two-time frames. STs who still expressed their negative emotion towards the end of teaching practicum did not fully intend to show that they did not get any benefits from it. They expressed such feeling to show that negative emotion led them to discover and familiarize themselves to be a teacher. This research suggests that preparation of teaching practicum, such as microteaching class needs to regard how to: deal with students, generate and convey teaching material, develop a lesson plan, choose appropriate teaching techniques, and evaluate the lesson. This will assist STs not to feel too anxious at the start of teaching practicum.Keywords: metaphor, positive and negative emotion, student teachers, teaching practicum